Continuous monitoring of cyanobacterial blooms: benefits and conditions for using fluorescence probes - Courtois, Sophie; Steinmann, Delphine; Cajon, Anne; van der Linden, Leon (Revue des sciences de l’eau / Journal of Water Science, 2017)
In situ fluorescence probes have attracted growing interest for the on-line monitoring of cyanobacteria in drinking water treatment plants. The probes rely on the fluorescence of pigments such as phycocyanin and chlorophyll-a to detect respectively cyanobacteria and green algae. They offer direct and simultaneous multiparameter measurements and opportunity for online monitoring which can enable water operators to improve cyanobacteria management during the drinking water process. However, fluorescence probes can be influenced by interference sources which may results in biased measurements. The impact of these factors on probe readings can make the calibration and validation process difficult for operators. Hence, the aim of the study was to calibrate and validate fluorescence probe performance (here YSI EXO2 probe) for varying laboratory grown phytoplankton species. Although good linear correlation between raw probe fluorescence readings and cyanobacteria cell concentrations was found, measurement bias was observed using this probe in water samples with high turbidity (62 NFU) or Dissolved Organic Carbon concentration (10 mg∙L-1). These data showed the potential of fluorescence probes deployment in cyanobacteria monitoring with a deeper understanding of the potential interference sources that is required to interpret data correctly.